Endovascular embolization of head and neck tumors - Lazzaro, Marc A.; Badruddin, Aamir; Zaidat, Osama O.; Darkhabani, Ziad; Pandya, Dhruvil J.; Lynch, John R. (Frontiers in Neurology, 2011)
Endovascular tumor embolization as adjunctive therapy for head and neck cancers is evolving and has become an important part of the tools available for their treatment. Careful study of tumor vascular anatomy and adhering to general principles of intra-arterial therapy can prove this approach to be effective and safe. Various embolic materials are available and can be suited for a given tumor and its vascular supply. This article aims to summarize current methods and agents used in endovascular head and neck tumor embolization and discuss important angiographic and treatment characteristics of selected common head and neck tumors.